Pengaruh Integrasi Wearable Technology terhadap Peningkatan Physical Literacy Siswa dalam Pembelajaran PJOK di SMPN 7 Blitar - Nur Ridwan Fauzen; Akbar Rohmad Aulia (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2025)
The development of digital technology has encouraged innovation in Physical Education, Sports, and Health (PJOK) learning, particularly through the utilization of wearable technology. This study aims to analyze the effect of wearable technology integration on improving students' physical literacy in PJOK learning at SMPN 7 Blitar. The research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The participants consisted of eighth-grade students divided into an experimental group and a control group. The experimental group participated in PJOK learning integrated with wearable technology, while the control group received conventional instruction. Data were collected through physical literacy assessments covering motor skills, physical fitness, knowledge of physical activity, motivation, and attitudes toward sports, supported by real-time physical activity data recorded by wearable devices. Data analysis was conducted using an independent sample t-test. The findings revealed that the average physical literacy score in the experimental group increased from 65 to 85, while the control group increased from 66 to 75. Statistical analysis showed a significance value of less than 0.05, indicating a significant difference between the two groups. Therefore, the integration of wearable technology was proven effective in enhancing students' physical literacy through more measurable, interactive, and data-driven learning processes.